Reparação óssea com membrana de poli (ácido lático-co-ácido glicólico) (PLGA) associada ao iodofórmio - Barbosa, Renato Zacura (2024)
Introduction: Inflammatory periapical lesions are among the most frequent in the oral and maxillofacial complex, with periapical cysts and granulomas accounting for twothirds of these lesions in the mandible region, where they are most frequent. Depending on the type of chronicity and the lesion present, and in cases where healing is not possible, surgical enucleation of the lesion may be necessary. Dental rehabilitation through the placement of osseointegrated implants significantly improves quality of life, restoring maxillofacial functions, including chewing and speech. This project proposes the unprecedented association of PLGA [Poly(lactic acid-co-glycolic acid], which is an alloplastic biomaterial with iodoform drug. Objective: To evaluate the osteoinductive action of PLGA membranes associated with iodoform in bone repair of upper maxillary and mandibular lesions. Methodology: This is an open, single-arm pilot trial of an outpatient surgical procedure with 04 dental patients with indication for bone repair of upper maxillary and mandibular lesions. The study was carried out by intervention of surgical repair technique, using the PLGA biomaterial associated with iodoform in the proportion of 50%. Results: The PLGA + iodoform particles developed presented stable mechanical characteristics and the iodoform was dispersed uniformly throughout the PLGA membrane indicating the homogeneity of this system. The PLGA + iodoform particles presented stable mechanical characteristics, Iodoform was dispersed evenly throughout the PLGA membrane, indicating the homogeneity of this system. Six months after the lesion curettage surgery and graft implantation, patients presented between 52% and 100% bone regeneration. Conclusion: The PLGA + iodoform combination presents osteoinductive, antiseptic and regenerative action and can be used for various bone lesions